The effectiveness of Snoezelen method on autism in children with autism spectrum disorder - zahra zarekhalili; Mehran Soleymani; Qorban HemmatiAlamdarlou; hassan yaghoubi (Ravānshināsī-i Afrād-i Istis̠nāyī, 2021)
The aim of this study was to investigate the effect of Snoezelen method on the symptoms of children with autism spectrum disorder. The research method was quasi-experimental with pre-test and post-test design with control group. The statistical population of the present study was all children with autism spectrum disorder, from which a sample of 30 people was selected by convenience sampling method and randomly assigned to the experimental and control groups. So that each group was 15 people and from both groups pre-test was performed and the experimental group received the Snoezelen method in 40 sessions while the control group was not presented with this intervention and at the end for both groups the post-test was performed. The instrument used in this study was the Gilliam (Garz) survival rating scale. Data analysis using univariate analysis of covariance and multivariate covariance showed that the mean scores of autism syndrome and its sub-comparisons (social interaction and communication) increased significantly and stereotyped behavior decreased P (<0/05). The findings indicate that the Snoezelen method improves autism in children with autism spectrum disorder. Therefore, it is recommended to design and implement Snoezelen program to improve autism.